The Impact of Cognitive Behavioral Sex Therapy on Decreasing Anxiety and Increasing Sexual Function in People with Vaginismus - Aliakbari Dehkordi1, Mahnaz; Mohammadi2*, Azam; Alipour1, Ahmad; Mohtashami2, Tayebeh (Shahroud Journal of Medical Sciences, 2017)
Background: The purpose of this study is to investigate the impacts cognitive behavioral sex therapy has on decreasing anxiety and increasing sexual function of people with vaginismus.Methods: The sample for this study was randomly chosen from a population of married women aged 20 to 35 years who were referred to both Farhangian Shahid Abuzari and Vali-Asr Therapeutic Centers in Shahr-e-Ray. Thirty female subjects were chosen and were divided into two groups; experimental group and control group. The pre-test was administered for both groups. The pre-test consisted of the items on Spielberger’s state-trait anxiety inventory (SATI) as well as the items on Rosen et al. (2000) Female Sexual Function Index. Then, the subjects in experimental group were treated with 12 sessions of cognitive behavioral therapy for vaginismus’ sexual dysfunctions. At the end, post-test was administered for both groups.Results: The results of covariance analysis demonstrated that cognitive behavioral therapy for sexual dysfunctions will lower the anxiety and, at the same time, it can also enhance sexual performance of females with vaginismus in the experimental group compared with control (P<0.05). Conclusions: Given the effects of cognitive behavioral therapy on people with vaginismu for improving sexual awareness about sexual function, it is recommended that young couples should be trained as this can help them to sustain their marital life and prevent sexual dysfunction.